Hubungan Faktor Demografi dan Motivasi terhadap Partisipasi Kader Asuhan Mandiri di Puskesmas Kecamatan Cakung Jakarta Timur Tahun 2020 - Gabe Gusmi Aprilla (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2022)
In 2017 and 2018, the Cakung Community Health Center has given self care orientation using the herbal garden and acupressure for 77 cadres from 5 sub-district namely Penggilingan, Pulo Gebang, Jatinegara, Ujung Menteng and West Cakung. Within 3-6 months of orientation, community health worker are expected to form self care groups. However, only one self care group was formed, namely in the Penggilingan sub-district, so the researchers were interested in analyzing the relationship between demographic factors and motivation of self care community health worker and their participation. This study uses primary data by filling out questionnaires and observing documents. The research design used a non-experimental quantitative approach with a cross sectional design. The results showed that most of them were housewives, married, > 46 years old, middle school education, income < minimum wage DKI and length of work < 5 years. Most of the low motivation 39 people (60%) and the remaining high motivation 26 people (40%) and low participation 33 people (50.8%) and the remaining high participation 32 people (49.2%). The length of work factor > 5 years increased participation 4 times, while the reward motivation increased 0.1 times. Conclusions : length of work and rewards for increasing participation. Suggestions : need for seed herbal plant, training, supervision, study tours, competitions the self care group and family gatherings to increase motivation for self care community health worker.